PENGARUH DESAIN KEMASAN TERHADAP IMPULSIVE BUYING PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNIVERSITAS TANJUNGPURA - Siti Aisah; Okianna Okianna; Jumardi Budiman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe research objectives were to determine: 1) attractive packaging design accordingto the perceptions of the Economic Education Study Program of the University ofTanjungpura, 2) impulsive buying of the Economic Education Study Program of theUniversity of Tanjungpura, 3) the effect of packaging design on impulsive buying ofthe Economic Education Study Program of the University of Tanjungpura, Theresearch method used is a quantitative form with the type of correlation research.Sampling techniques with simple random sampling as many as 80 respondents. Theresults showed: (1) attractive packaging design according to student perceptions wasincluded in the very high category of 82.48%, (2) impulsive buying of students was inthe high category of 70.38%, (3) Based on the results of hypothesis testing using the ttest showed that the value of t count > t table or 2.542 > 1.9908, meaning that H0 isrejected and Ha is accepted. The correlation coefficient value of 0.277 is a lowrelationship category. The coefficient of determination is 0.077 or 7.7%. So it can beconcluded that packaging design has a positive and significant effect on impulsivebuying.Keywords: Packaging Design and Impulsive Buying